Notary's Obligations for The Drafting of a Sale-Purchase Agreement Deed in Connection with Regional Retribution - Nontji, Surya La; Witasari, Aryani (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. This study analyzes the obligations and responsibilities of notaries in making a Deed of Sale and Purchase Agreement (PPJB) based on Regional Regulation Number 8 of 2023 and the Notary Law (UUJN). In addition, this study identifies the forms of sanctions that can be imposed on notaries if violations occur and evaluates the effectiveness of supervision and law enforcement in the notary profession. By understanding the regulations and their implementation, this study is expected to provide recommendations to improve the professionalism of notaries and legal protection for parties conducting land sale and purchase transactions through PPJB. The approach used is normative juridical with qualitative analysis methods. Data were obtained through literature studies, including laws and regulations, court decisions, and related legal literature. The analysis was carried out by examining the obligations of notaries based on regulations and comparing their implementation in practice. In addition, the study examines the form of sanctions against notaries in violation of the making of PPJB and the role of the Notary Supervisory Board in ensuring compliance with regulations. The results of the study show that notaries have an important role in ensuring the validity and legal certainty of PPJB. Compliance with the law protects the rights of the parties and prevents disputes, but obstacles such as lack of documents from related parties and potential abuse of authority still occur. Administrative, civil, and criminal sanctions regulated in the UUJN and Regional Regulation Number 8 of 2023 need to be implemented more effectively in order to provide a deterrent effect and increase the accountability of the notary profession.Keywords: Deed of Agreement; Notary Obligations; Retribution.